Therapeutic Modulation of the Complement System in Kidney Transplantation: Clinical Indications and Emerging Drug Leads - Tatapudi, Vasishta S.; Montgomery, Robert A. (Frontiers in Immunology, 2019)
The complement system is integral to innate immunity, and it is an essential deterrent against infections. The complement apparatus comprises greater than thirty fluid-phase and surface-bound elements that also engage with the adaptive immune system, clear harmful immune complexes, and orchestrate several salutary physiological processes. An imbalance in the complement system’s tightly regulated machinery and the consequent unrestrained complement activation underpins the pathogenesis of a wide array of inflammatory, autoimmune, neoplastic and degenerative disorders. Antibody mediated rejection is a leading cause of graft failure in kidney transplantation. Complement induced inflammation and endothelial injury have emerged as the primary mechanism in the pathogenesis of this form of rejection. Researchers in the field of transplantation are now trying to define the role and efficacy of complement targeting agents in the prevention and treatment of rejection and other complement related conditions that lead to graft injury. Here, we detail the current clinical indications for complement therapeutics and the scope of existing and emerging therapies that target the complement system, focusing on kidney transplantation.